Evaporation and dispersion of respiratory droplets from coughing. (23rd March 2016) - Liu, L.; Wei, J.; Li, Y.; Ooi, A.
Abstract: Understanding how respiratory droplets become droplet nuclei and their dispersion is essential for understanding the mechanisms and control of disease transmission via droplet‐borne and airborne routes. A theoretical model was developed to estimate the size of droplet nuclei and their dispersion as a function of the ambient humidity and droplet composition. The model‐predicted dried droplet nuclei size was 32% of the original diameter, which agrees with the maximum residue size in the classic study by Duguid, 1946, Edinburg Med. J., 52, 335 and the validation experiment in this study, but is smaller than the 50% size predicted by Nicas et al., 2005, J. Occup. Environ. Hyg ., 2, 143. The droplet nuclei size at a relative humidity of 90% (25°C) could be 30% larger than the size of the same droplet at a relative humidity of less than 67.3% (25°C). The trajectories of respiratory droplets in a cough jet are significantly affected by turbulence, which promotes the wide dispersion of droplets. We found that medium‐sized droplets (e.g., 60  μ m) are more influenced by humidity than are smaller and larger droplets, while large droplets (≥100  μ m), whose travel is less influenced by humidity, quickly settle out of the jet.